2021
DOI: 10.19030/jabr.v37i6.10395
|View full text |Cite
|
Sign up to set email alerts
|

Bank Capital Adequacy: The Impact Of Fundamental And Regulatory Factors In A Developing Country

Abstract: This paper provides evidence that the overcapitalized banks are much more sensitive to fundamental factors rather than to the regulatory requirements such the Basle’s Accord requirements, which raises the question of whether Basel’s limits are sufficient to minimize financial crises. Also, keeping buffers against falling below the minimum requirements appear to be of second order importance. Three fundamental factors affect capital adequacy in Jordan; risk, return and activity. Risk indicators drive the capita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Some of this review pointed out that low market shares and inadequate capital levels affect positively the level of bankruptcy rate of community banks (Lucas, 2019;Ahmet & Harun, 2019). This is due to the fact that when there is low market share and inadequate capital levels, the respective bank fails to expand business and compete with others in terms of lending portfolio and deposits mobilization, thus exposing to the potential vulnerability of bankruptcy (Alzoubi, 2021). In that regard, community bank's management is responsible for creating fundamental centricity for increasing performance through increasing market share, thus assisting to raise strength to withstand external shocks emanating from the macroeconomic environment (Leonard et al 2017, Ahmet & Harun, 2019.…”
Section: Theoretical and Conceptual Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of this review pointed out that low market shares and inadequate capital levels affect positively the level of bankruptcy rate of community banks (Lucas, 2019;Ahmet & Harun, 2019). This is due to the fact that when there is low market share and inadequate capital levels, the respective bank fails to expand business and compete with others in terms of lending portfolio and deposits mobilization, thus exposing to the potential vulnerability of bankruptcy (Alzoubi, 2021). In that regard, community bank's management is responsible for creating fundamental centricity for increasing performance through increasing market share, thus assisting to raise strength to withstand external shocks emanating from the macroeconomic environment (Leonard et al 2017, Ahmet & Harun, 2019.…”
Section: Theoretical and Conceptual Backgroundmentioning
confidence: 99%
“…In the same manner, it has been stated that the Regulator has the role to intervene when the banks indicate signals of bankruptcy, however this risk remains high, as evidenced by the continuation of increases in the level of undercapitalization and low market share of some community banks in terms of deposits, assets and loan portfolio (Simplice & Odhiambo, 2019). According to Alzoubi (2021), Ahmet and Harun (2019) detailed that the capital adequacy of banks is very important for efficient bank operations based on the ground that total capital levels, normally grow at a high rate depending on the profitability level of the respective bank. Further, according to various literature reviews such as Awadzie (2021) indicated that the capital adequacy ratio has a significant positive relationship with community bank financial performance; thus, when the bank has a low capital position, it may frequently experience a high bankruptcy rate.…”
Section: Empirical Review and Hypothesis Developmentmentioning
confidence: 99%
“…The evidence is very limited. Dam and Koetter (2012) claim that the bailing out financial institutions during the 2008 financial crisis proves two important lesson; first that governments were forced to bail out SIBs; second, whenever governments’ subsidies are expected, banks will be induced to take more risk due to moral hazard (Alzoubi, 2021). Bailing out undermines market discipline, distorts competition, and raise the probability of financial distress (Lambert et al, 2014; Ueda & Weder di Mauro, 2013).…”
Section: Future Research Directionsmentioning
confidence: 99%
“…First, the feasibility of raising the capital adequacy requirements significantly from the current 12.5% in Basel III to 20% or 25% and address the need to impose an even higher ratio to SIBs (Alzoubi, 2021; Passmore & von Hafften, 2017, 2019). Limited evidence is available on this subject.…”
Section: Future Research Directionsmentioning
confidence: 99%
See 1 more Smart Citation